Five year outcomes of the subcutaneous implantable cardioverter-defibrillator EFFORTLESS (evaluation of factors impacting clinical outcome and cost effectiveness of the S-ICD) registry. (24th May 2021) - Lambiase, P; Theuns, DAMJ; Murgatroyd, FD; Barr, CS; Eckardt, L; Neuzil, P; Scholten, MF; Hood, MA; Kuschyk, J; Brisben, A; Carter, N; Knops, RE; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Boston Scientific OnBehalf: EFFORTLESS Registry Introduction: Patients (pts) implanted with transvenous (TV) implantable cardioverter-defibrillator (ICD) experience complications (Cx) associated with TV leads and inappropriate shocks (IAS) for atrial fibrillation (AF) or other supraventricular tachycardias (SVT). The EFFORTLESS S-ICD Registry is a 5-year (yr) follow-up (f/u) study of pts implanted with the subcutaneous ICD (S-ICD). Purpose: To report on the 5-yr outcomes of pts with a wide range of S-ICD indications implanted with early generation devices. Methods: Pts were enrolled at 43 centers February 2011-December 2014. Kaplan-Meier Cx, appropriate shock (AS), and IAS rates are reported. Results: 994 pts (495 retrospective) were enrolled in the EFFORTLESS study and 984 pts (28% female, 48 ± 17 yrs, BMI 27 ± 6 kg/m2, ejection fraction 43 ± 18%) underwent S-ICD implantation. Mean study f/u was 4.4 ± 1.6 yrs. The pt cohort had diverse etiologies: 31% ischemic heart disease, 19% non-ischemic cardiomyopathy, 11% hypertrophic cardiomyopathy, 17% channelopathies, and 20% of pts miscellaneous. Total system- and procedure-related Cx (table) were 9.4% at 5 yrs. AS and IAS rates at 5 yrs were 15.9% and 16.9%, respectively and the IAS rates for AF/SVT and t wave oversensing were 3.1% and 5.8%, respectively. More pts experienced Cx and IAS in the first yr than in yrs 2-5 altogether (8.7 vs 8.2%), the most common as a result of discomfort/erosion (38%), IAS (26%), system infection (9%), and premature battery depletion (9%). Of these late Cx, 74% were experienced by retrospective pts. Spontaneous conversion efficacy for the first shock and final shocks was 89.7% and 97.7%. Of the 91 (9.2%) deaths reported, none were associated with the S-ICD system or procedure. Cause of death was cardiac for 40 pts, non-cardiac for 40 pts, other for 4 pts, and unknown for 7 pts. Only 20 (2.0%) pts had their S-ICD replaced for a TV device for pacing: 4 bradycardia, 7 anti-tachycardia, and 9 for biventricular pacing. Conclusions: The EFFORTLESS registry provides 5-year follow-up for a diverse, large, multinational S-ICD registry. Complications primarily occurred in the first year but remained low through 5 years. Inappropriate shock rates were typically observed in older generation devices prior to introduction of the SMART Pass filter. Replacement for TV-ICD due to the need for pacing was rare.